Effective Cross-linking Dyeing Method for Jute Fabric with Reactive Dyes - Uddin, Md. Kamal; Hossain, H. M. Zakir; Sarker, Jahid; Jahan, Fatema Nusrat; Sultana, Nayar (European Scientific Journal, ESJ, 2019)
With a view to develop an effective dyeing method for jute fabric, jute fabric known as Carpet Backing Cloth (CBC), made from jute fiber, was first desized, scoured, and bleached with hydrogen peroxide. Simultaneous dyeing and finishing methods were carried out using various reactive dyes with some cross-linking agents like Fixapret CPN, Fixapret ECOs of BASF, and Indosol E-50 Powder (Sandoz) along with some catalysts (MgCl2, 6H2O) and softening agent. Three types of cross-linking methods such as dry, moist, and wet were employed. The cross-linking method was optimized by treatment of bleached CBC with different concentrations of cross-linking agents and catalysts applying pad-dry-cure method at different temperatures. Significant improvement was found in dye fixation rate, dye fastness (washing, rubbing, light and perspiration) properties, and tensile strength of cross-linked dyed jute fabric. Regarding all dyeing and physical properties, Indosol E-50 powder along with various reactive dyes achieved highly satisfactory results. Fixapret CPN may also be comparable to Indosol E-50 powder.